2009
DOI: 10.1111/j.1440-1584.2009.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Approach to treatment of mental illness and substance dependence in remote Indigenous communities: Results of a mixed methods study

Abstract: These results suggest that MCP is an effective treatment for Indigenous people with mental illness and provide insight into the experience of mental illness in remote communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(159 citation statements)
references
References 26 publications
1
158
0
Order By: Relevance
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these Eley et al (2010) detected improved outcomes for Study 1 but not Study 2 or for two subsequent iterations of the program. For eight interventions described in the study, observed improvements were statistically significant (O'Dea 1984; Lee et al 1994;Rowley et al 2001;d'Espaignet et al 2003;Nagel et al 2009;Eley et al 2010;Dimer et al 2013;Sun and Buys 2013). Two studies where statistical analyses were not conducted show positive directions of effects in health and wellbeing outcomes (Nel and Pashen 2003;Preuss and Brown 2006) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…One RCT (Nagel et al 2009), one cluster RCT (Kiran and Knights 2010) and two studies with non-randomised controls (Lee et al 1994;d'Espaignet et al 2003) were included. Other papers report case series or serial cross-sectional data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations